Insulin increases homocysteine levels in a dose-dependent manner in diabetic rats - Gursu, MF; Baydas, G; Cikim, G; Canatan, H (Elsevier Science Inc, 2002)
Background. Even moderate increases in levels of homocysteine cause cardiovascular degeneration. Various genetic and nutritional factors affect plasma homocysteine concentrations, and hyperhomocysteinemia damages vascular endothelial cells; hence their functions are disrupted. In diabetes mellitus, homocysteine metabolism is altered and as a result, more severe diabetic complications are expected when hyperhomocysteinemia occurs. Methods. In the present study we experimentally induced diabetes in rats and examined effects of low or high dose of insulin administration on homocysteine metabolism. Results. We determined that homocysteine levels were reduced in STZ-induced diabetic rats. This reduction was normalized by insulin in a dose-dependent manner. On the other hand, increased levels of lipid parameters (cholesterol, triglycerides, HDL) were reduced by insulin. Conclusions. Hcy level in experimentally induced insulin-dependent diabetes mellitus is decreased and injection of insulin normalizes Hcy levels in a dose-dependent manner. We speculate that insulin increases activities of enzymes of transsulfuration and remethylation reactions and hence speeds up conversion of Hcy to methionine and cysteine. (C) 2002 IMSS. Published by Elsevier Science Inc.
Keywords: homocysteine; diabetes mellitus; insulin